A Study on the Psychological Contract of Administrative Personnel in Vocational Education Institute - Wu, Mingchang; Nurlaela, Luthfiyah (Journal of Technical Education and Training, 2020)
Previous studies consistently identified that psychological contract played a crucial role to facilitate people’s loyalty and commitment, job dedication, and finally career achievement. Its influential factors and enhancement approaches consequently attracted broad attention of professorates in the business world and educational fields. This study was conducted to identify the traits and internal structure of psychological contract for administrative personnel in vocational education institutes at higher educational level. The questionnaire was employed to collect research data from a sample of 165 administrative personnel of the vocational institutes located in the central Taiwan. Undertaken were a series of data analyses including reliability and validity analyses, descriptive statistics, CFA factor analysis, and SEM statistics according to the research purpose. These data analyses led to the following conclusions: 1) These administrative personnel, who traditionally pursued academic achievement and professional autonomy, possessed a middle level of the psychological contract for overall; 2) Their psychological contract of this group was characterised with the significant and positive relationships among the three major domains; 3) this academic personnel were inclined to the transactional psychological contract rather than relational one; they are more practical and pragmatic to manage their professional careers; and 4) The domain factor of reciprocal commitment and obligations was approved to play the crucial role of the mediator between job recognition and relationships. Based on the conclusions, this study finally provided several practical suggestions to foster faculty members’ career development and university efficacy.